THE INFLUENCE OF STUDY MOTIVATION, STUDY HABITS, AND CONFIDENCE ON LEARNING OUTCOMES IN CLASSROOM TAX ADMINISTRATION SUBJECTS XI ACCOUNTING FOR SMK NEGERI 22 AND 51 JAKARTA. - Khotimah, Ulfah Husnul; Susanti, Santi; Zulaihati, Sri (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine whether there is an influence between learning motivation, study habits, and self-confidence on learning outcomes in class XI students of SMKN 22 and 51 Jakarta. The research period was from March 2021-June 2021. The approach used in this research is a quantitative approach with a survey method. The affordable population for this study were all class XI SMKN 22 and 51 Jakarta, totaling 144 students. The sampling technique used proportional stratified random sampling so that the sample obtained was 108 students. The instrument used to obtain data on the variable X1 (Learning Motivation), Variable X2 (Study Habits), and Variable X3 (Self Confidence) were measured using a Likert scale using a questionnaire that had been tested for validity and reliability. Multiple regression equation model = 76.321 + 0.060X1 + 0.046X2 + 0.078X3. Normality and linearity tests show that the data are normally distributed and have a linear relationship. The results of the T test indicate that learning motivation, study habits, and self- confidence had a positive influence on learning outcomes. Then, the results of the F test show that learning motivation, study habits, and self-confidence have a significant effect on learning outcomes simultaneously. The results of this study indicate that learning motivation, study habits, and self- confidence have a contribution of 36.2% to learning outcomes.